The impacts of competition, efficiency, and risk towards bank’s performance in Indonesia - Eko Cristian; Wirdy Leonarsan; Sung Suk Kim (Jurnal Keuangan dan Perbankan, 2020)
Banks in Indonesia provide more than 40 percent of funding in economy. Sustainable performance of commercial banks is important because they have large effects on the growth of whole economy. The purpose of this study is to investigate how the effects of competition, efficiency, and risk on performance of bank in Indonesia forty-six public commercial banks in Indonesia Stock Exchange (IDX) between 2002-2018. One-step system generalized method of moments are used to handle endogeneity in dynamic panel model. Competition of non-interest income market influence negatively on bank performance. Cost efficiency and revenue efficiency does not affect bank performance. Profit efficiency positively effect on net interest margin, but not return on assets. Credit risk negatively effects on ROA, not on NIM. Capital risk negatively effects on NIM, but not ROA. Insolvency risk negatively effects on NIM, not on ROA. While, loans and deposit market’s competition and liquidity risk does not affect bank performance in Indonesia. JEL Classification: G21, G32DOI: https://doi.org/10.26905/jkdp.v24i4.4903